Pemodelan Matematika Bekam Pada Kanker Nasofaring Dan Kontribusinya Bagi Penanganan Kanker Nasofaring - Sugiyanto, Mr. (UIN Sunan Kalijaga Yogyakarta, 2015)
Cancer / Nasopharyngeal carcinoma is a cancer of the first malignancy in the head and neck. It is located in nasopharynx, behind the nose. Ebstein Barr virus is one of the triggers of this carcinoma. Cupping is a process of detoxification of toxins in the body so as immunity increases. Quite a lot of the sayings of the Prophet Muhammad about the cupping. The method used in this study mathematical modeling nasofang carcinoma cell level. There are two cases which are modeled in this case, the first case of low immunity without cupping, and second case low immunity with the cupping. The first case of low immunity without a cupping here are seven sub-populations that happened, ie normal cells, lesion cells, low dysplastic cells, the infected cells, high dysplastic cells, invasive carcinoma cells and viruses. Meanwhile, two cases of low immunity with the cupping there are five sub-populations, ie normal cells, lesion cells, low dysplastic cells, the infected cells, and viruses.